Low Handgrip Strength Is Associated with Higher Liver Enzyme Concentrations in Us Adolescents - Garcia-Hermoso, A (Springer Nature, 2022)
Background: Increasing evidence highlights the role of muscular strength as a protective factor for cardiometabolic health in adolescents. However, it is not known the relationship between liver enzyme concentrations, liver disease risk factors, and muscular strength among young populations. The aim of this study was to determine the association between muscle strength and liver enzymes and chronic liver disease risk among US adolescents. Methods: Data from the NHANES cross-sectional study (2011–2014) was used. A total of 1270 adolescents were included in the final analysis (12–17 years old). Absolute handgrip strength (kg) was normalized according to body composition parameters by body weight [NHSw], whole-body fat [NHSf], and trunk fat [NHSt]). Results: In boys, handgrip strength was inversely associated with higher values of aspartate aminotransferase (AST) and gamma glutamyl transpeptidase (GGT) for all estimations of muscle strength (NHSw, NHSf, and NHSt) (p < 0.050). Likewise, boys with high and intermediate NHSw, NHSf, and NHSt presented lower AST and GGT than their counterparts with low handgrip strength (p < 0.050). Conclusions: Our findings highlight the importance of muscular strength during adolescence since they could help in developing better liver enzyme profiles among adolescent population. Impact: Our research suggests that US adolescents with low handgrip strength have higher values of liver enzymes as well as a higher prevalence of chronic liver disease.These findings are clinically meaningful and highlight the importance of muscular strength during adolescence since they could help in developing better liver enzyme profiles among young populations. © 2021, The Author(s), under exclusive licence to the International Pediatric Research Foundation, Inc.